Enhancement of the Bio-Responsiveness of PCL Nanofibers via the Combination of a Thiol Plasma-Polymerized Coating and Fibronectin Immobilization - Pegah Zahedifar; Rino Morent; Sheida Aliakbarshirazi; Rouba Ghobeira; Nathalie De Geyter (Applied Surface Science Advances)
To enhance cellular interactions with scaffolds used in tissue engineering, scaffold morphology should mimic the extracellular matrix (ECM) and the scaffold should possess appropriate bulk and surface properties. This study aimed to improve the physiochemical and bio-responsive properties of hydrophobic electrospun polycaprolactone (PCL) nanofibers by applying a thiol-rich coating using dielectric barrier discharge (DBD) plasma polymerization at medium pressures with 1-propanethiol as monomer. The effects of carrier gas type, DBD chamber pressure, treatment time, and the Yasuda parameter (a combination of precursor flow rate and discharge power) on the plasma polymerization process were systematically investigated. Optimal deposition conditions were determined by analyzing the coated nanofibers using scanning electron microscopy (SEM), water contact angle (WCA) measurements, and X-ray photoelectron spectroscopy (XPS) aiming to achieve the highest thiol density coating while preserving the nanofibrous morphology. Our findings indicated that using argon as carrier gas resulted in a thicker coating with a significantly higher sulphur content compared to when helium was used as the carrier gas. Increasing deposition time from 5 to 15 minutes initially increased coating thickness, hydrophilicity, and sulphur content, reaching a saturation point after 10 minutes. The optimal chamber pressure was observed to be 10 kPa, as higher pressures caused nanofiber melting. Yasuda parameter analysis revealed that an intermediate value of 72 MJ/kg provided optimal thiol incorporation and coating stability. In a final step of the study, the effectiveness of the thiol coatings and subsequent fibronectin immobilization in enhancing Schwann cell adhesion and proliferation was assessed. The thiol-coated substrates demonstrated superior protein immobilization and significantly improved cell responses. Post-fibronectin immobilization, these substrates exhibited the highest cell viability, adhesion, and proliferation. These results highlight the synergistic effect of thiol plasma polymerization and fibronectin immobilization in promoting cellular responses on PCL nanofibers, underscoring their potential as a surface modification strategy for tissue engineering applications.